Fungsi Badan Kepegawaian dan Pengembangan SDM dalam Melakukan Mediasi pada Proses Perceraian PNS di Lingkungan Pemerintah Kabupaten Tana Tidung - Somibeda Lamadokend, Juliana; Sabil , Ibnu; Sastrawan Putra, Anak Agung Made (Universitas Terbuka, 2022)
Marriage according to Law Number 1 of 1974 is an inner and outer bond between a man and a woman as husband and wife to live a perfect, happy, and eternal life. Not all marriages can run as expected because there is no agreement or conflicting behavior that results in divorce in both the general public and civil servants. This study aims to describe and analyze staffing policies in fostering household harmony and support improving employee performance, analyze the factors causing civil servant divorce, analyze the mediation process carried out by BKPSDM as a form of regional organizational function in the civil servant divorce process and analyze obstacles and solutions. In mediating the divorce process for civil servants within the Tana Tidung Regency Goverment. This study uses a qualitative descriptive method with data collection techniques through interviews, observation and documentation. This study concludes that the government policy of Tana Tidung Regency in fostering household harmony is carried out through religious activities, giving leave, counseling guidance, and socialization about household harmony. Factors causing civil servant divorce include infidelity, economy, one party being a drug addict, and differences in principles, ideology, and religion. BKPSDM as a mediator uses the 5 mediation principles of David Spencer and Michael Brogan in the civil servant divorce apllication process. The obstacles faced werw that one of the parties was unable to attend, and parties were uncooperative, unable to accept suggestions, and incomplete administrative requirements. The solution is to make a summons to the parties concerned, bring other parties to obtain additional information, and contact employees to complete the requirements for submitting a divorce permit so that the next process can be carried out.